T cell detection of a B-cell tropic virus infection: newly-synthesised versus mature viral proteins as antigen sources for CD4 and CD8 epitope display. - Laura K Mackay; Heather M Long; Jill M Brooks; Graham S Taylor; Carol S Leung; Adrienne Chen; Fred Wang; Alan B Rickinson (PLoS Pathogens)
Viruses that naturally infect cells expressing both MHC I and MHC II molecules render themselves potentially visible to both CD8+ and CD4+ T cells through the de novo expression of viral antigens. Here we use one such pathogen, the B-lymphotropic Epstein-Barr virus (EBV), to examine the kinetics of these processes in the virally-infected cell, comparing newly synthesised polypeptides versus the mature protein pool as viral antigen sources for MHC I- and MHC II-restricted presentation. EBV-transformed B cell lines were established in which the expression of two cognate EBV antigens, EBNA1 and EBNA3B, could be induced and then completely suppressed by doxycycline-regulation. These cells were used as targets for CD8+ and CD4+ T cell clones to a range of EBNA1 and EBNA3B epitopes. For both antigens, when synthesis was induced, CD8 epitope display rose quickly to near maximum within 24 h, well before steady state levels of mature protein had been reached, whereas CD4 epitope presentation was delayed by 36-48 h and rose only slowly thereafter. When antigen expression was suppressed, despite the persistence of mature protein, CD8 epitope display fell rapidly at rates similar to that seen for the MHC I/epitope half-life in peptide pulse-chase experiments. By contrast, CD4 epitope display persisted for many days and, following peptide stripping, recovered well on cells in the absence of new antigen synthesis. We infer that, in virally-infected MHC I/II-positive cells, newly-synthesised polypeptides are the dominant source of antigen feeding the MHC I pathway, whereas the MHC II pathway is fed by the mature protein pool. Hence, newly-infected cells are rapidly visible only to the CD8 response; by contrast, latent infections, in which viral gene expression has been extinguished yet viral proteins persist, will remain visible to CD4+ T cells.